2022
DOI: 10.1212/nxi.0000000000001146
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Neuropathy Evaluations of Patients With Prolonged Long COVID

Abstract: Background and ObjectivesRecovery from severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection appears exponential, leaving a tail of patients reporting various long COVID symptoms including unexplained fatigue/exertional intolerance and dysautonomic and sensory concerns. Indirect evidence links long COVID to incident polyneuropathy affecting the small-fiber (sensory/autonomic) axons.MethodsWe analyzed cross-sectional and longitudinal data from patients with World Health Organization (WHO)-defin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
128
0
11

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(159 citation statements)
references
References 8 publications
6
128
0
11
Order By: Relevance
“…Two groups have found evidence of a small fiber neuropathy among those with COVID-19 associated with abnormal autonomic testing. 51, 52…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Two groups have found evidence of a small fiber neuropathy among those with COVID-19 associated with abnormal autonomic testing. 51, 52…”
Section: Discussionmentioning
confidence: 99%
“…Two groups have found evidence of a small fiber neuropathy among those with COVID-19 associated with abnormal autonomic testing. 51,52 Autonomic dysfunction could also occur via direct infection of autonomic regulatory regions of the brainstem tone, which are anatomically close to the cribiform plate and the olfactory nerves.…”
Section: Findings Of Vascular Dysfunctionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various studies have implicated induction of neuroinflammation as a likely mediator of altered neurologic function associated with COVID-19 neuropathophysiology (2,(73)(74)(75)(76)(77). This idea has gained credence from several human postmortem neuropathologic studies that have not demonstrated widespread infection of either neurons or glia as the basis for long neurologic COVID-19 (31,76,78).…”
Section: Discussionmentioning
confidence: 99%
“…Mild encephalopathies with transient symptoms such as altered consciousness (19.1% of 841 patients) or bradypsychia and disorientation (10.1% of 841 patients) were found to occur rather commonly often accompanied by findings of unspecific T2/FLAIR hyperintensity (35% of 20 patients) and ischemic infarcts (31% of 108 patients) in neuroimaging (Romero-Sanchez et al 2020 ; Mahammedi et al 2020 ; Radmanesh et al 2020 ). Severe COVID-19-associated encephalopathies including ADEM or acute necrotizing encephalopathies and poly(radiculo)neuropathies as GBS or other acute neuropathies (multifocal demyelinating or small fiber polyneuropathy) have also been described in several case reports with an estimated prevalence of 0.1–1% in western countries within 6 weeks of confirmed infection (Mahapure et al 2021 ; Parsons et al 2020 ; Shahali et al 2021 ; Toscano et al 2020 ; Camdessanche et al 2020 ; Hayley and Sun 2021 ; Dixon et al 2020 ; Poyiadji et al 2020 ; Oaklander et al 2022 ). For some entities, a causative relationship to prior SARS-CoV-2 infection is less clear.…”
Section: Introductionmentioning
confidence: 94%